THE LEGAL STATUS OF ECONOMIC BOYCOTT AGAINST MAHARIB AHL E KUFFAR (INFIDELS) IN THE WORLD TODAY: A RESEARCH STUDY IN THE CONTEXT OF ISLAMIC JURISPRUDENCE (Al-Aasar, 2025)
A stable economy is the backbone for the development and prosperity of any nation. A stable economy means that the economic condition of a country is strong, organized and sustainable, which can accelerate the growth and development. In world today, only those countries are considered developed whose economy is stable. The foundation of a stable economy is based on agricultural development, industrial production, trade relations, and modern technology that provide opportunities for overall development. The Quran and Sunnah provide guidelines on economic interactions with non-Muslims, balancing principles of justice, necessity, and strategic interest. Historically, economic boycotts were used both by the Quraish against Muslims and by the Prophet (ﷺ) and his companions as a strategic tool, such as the boycott of Jewish tribes who violated treaties in Madinah. Islamic jurists discuss the permissibility of such boycotts based on objectives like deterring harm, supporting oppressed Muslims, and preserving Islamic economic independence. However, Islamic teachings also emphasize fairness, fulfilment of contracts, and the prohibition of unjust harm. This article investigate the origins, development, of boycott and legal and ethical dimensions of economic boycott against Maharib Ahl e kuffar (infidels). With that it also explore and analysing the classical and contemporary scholarly opinions according to Islamic Jurisprudence that asses their applicability in the Muslim world today.